2011
DOI: 10.1007/s00267-011-9689-1
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding and Integrating Local Perceptions of Trees and Forests into Incentives for Sustainable Landscape Management

Abstract: We examine five forested landscapes in Africa (Cameroon, Madagascar, and Tanzania) and Asia (Indonesia and Laos) at different stages of landscape change. In all five areas, forest cover (outside of protected areas) continues to decrease despite local people’s recognition of the importance of forest products and services. After forest conversion, agroforestry systems and fallows provide multiple functions and valued products, and retain significant biodiversity. But there are indications that such land use is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 39 publications
1
62
1
1
Order By: Relevance
“…In 2007, the International Union for Conservation of Nature launched the "Landscapes and Livelihoods" initiative (www.iucn.org/about/work/ programmes/forest/fp_our_work/fp_our_ work_initiatives/fp_our_work_ll/), explicitly addressing the dual goals of environmental conservation and poverty alleviation. Similarly, a Center for International Forestry Research/World Agroforestry Centre initiative, the "Landscape Mosaics" project, with case studies from Cameroon, Tanzania, Madagascar, Laos, and Indonesia, focused on wider landscape approaches to integrate agriculture, conservation, and other functions (45).…”
Section: Resultsmentioning
confidence: 99%
“…In 2007, the International Union for Conservation of Nature launched the "Landscapes and Livelihoods" initiative (www.iucn.org/about/work/ programmes/forest/fp_our_work/fp_our_ work_initiatives/fp_our_work_ll/), explicitly addressing the dual goals of environmental conservation and poverty alleviation. Similarly, a Center for International Forestry Research/World Agroforestry Centre initiative, the "Landscape Mosaics" project, with case studies from Cameroon, Tanzania, Madagascar, Laos, and Indonesia, focused on wider landscape approaches to integrate agriculture, conservation, and other functions (45).…”
Section: Resultsmentioning
confidence: 99%
“…While some farmers regret forest and biodiversity loss, they are often driven by the simple desire to improve individual well-being, turning to agricultural practices, which are often perceived as providing faster and more secure returns (Meijaard et al 2013). When agriculture is the only option to alleviate financial pressures, policies must consider macroeconomic factors to optimize land-use planning (Pfund 2011). A study in Costa Rica found that rather than the funding from Payments for Ecosystem Services (PSA), forest recovery in agricultural land was influenced more by the simultaneous decrease in cattle profits and increase in tourism industry, a tenuous recovery that may be negatively impacted by shifts in markets for cattle and tourism Calvo-Alvarado 2009).…”
Section: Projects That Attempt To Promote Trees In Landscapesmentioning
confidence: 99%
“…The ecological damage and reduction of diversity of the ongoing forest conversion is well noted, but continues despite increasing recognition of the importance of forest conservation and restoration. However, a solution is far more complicated than simply reducing agricultural land or increasing protection of forests (Pfund et al 2011).…”
Section: On-farm Tree Cover and Services Providedmentioning
confidence: 99%
See 2 more Smart Citations